A study on correlation between screen time duration and school performance among primary school children at Tamil Nadu, India - Kumar, S. Santha; Shirley, S. Alph (International Journal of Contemporary Pediatrics, 2019)
Background: In recent times, one of the factors implied in poor school performance in children is increasing screen time. Objective of the study was to find the association of screen time duration with school performance among primary school children in the state of Tamil Nadu, India. Methods: This cross-sectional observational study was conducted among 134 primary school students at the state of Tamil Nadu, India from June 2019 to August 2019. Data regarding screen time were collected from the parents and school performance from teachers using a predesigned questionnaire. The data collected were analyzed with suitable statistical methods using SPSS 25 software. Results: Of the 134 children, 72(53.7%) were male and 62(46.3%) female children. 52(38.8%) were in the age group of 6 to 7 years, 47(35.1%) in the age group of 8 to 9 years and 35(26.1%) in the age group of 10 to 11 years. Majority of the children (56.7%) had an average daily screen time of >120 minutes followed by 61 to 120 minutes (29.1%) and ≤60 minutes (14.2%). Based on composite academic performance, 23(17.2%) children were categorized as having poor academic performance, 71(52.9%) as average and 40(29.9%) as good academic performance. There was no statistically significant correlation of screen time duration with composite academic performance and academic performance in mathematics, science and language. (p Value >0.05). Conclusions: There was no significant correlation between screen time duration and school performance in primary school children in this study. Further studies are required to find the influence of screen time on various domains of learning and on long term cognition and educational achievement.